2003
DOI: 10.1590/s0034-72992003000400016
|View full text |Cite
|
Sign up to set email alerts
|

Alterações na audiometria de tronco encefálico em mulheres adultas com hipotireoidismo subclínico

Abstract: A correlação entre perda auditiva e distúrbios adquiridos da glândula tireóide tem sido tema de interesse há muito tempo na Medicina. Diversos trabalhos foram dedicados à investigação audiológica de pacientes com hipotireoidismo, mas poucos autores abordaram a forma subclínica desta doença utilizando a audiometria de tronco encefálico (ABR). Objetivo: Avaliar se ocorrem ou não alterações na ABR em mulheres normoacúsicas com hipotireoidismo subclínico não tratado quando comparadas a mulheres sem doença endócrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
3
0
3
Order By: Relevance
“…Diğer taraftan Figueiredo ve ark. [18] 23 subklinik hipotiroidili hasta üzerinde yaptıkları bir çalışmada BAEPs testinde III ve V dalgada gecikme ve I-III, III-V ve I-V dalgalar arası anlamlı değişiklik izlendiğini belirtmişlerdir.…”
Section: Discussionunclassified
“…Diğer taraftan Figueiredo ve ark. [18] 23 subklinik hipotiroidili hasta üzerinde yaptıkları bir çalışmada BAEPs testinde III ve V dalgada gecikme ve I-III, III-V ve I-V dalgalar arası anlamlı değişiklik izlendiğini belirtmişlerdir.…”
Section: Discussionunclassified
“…And one case also had deterioration in hearing. Further it was observed that the thyroxine treatment influences the hearing maximally at 1000 Hz, the frequency at which 31 ears had a significant gain of 10 db or more There are diverse views regarding improvement in hearing in hypothyroid patients with thyroxine treatment [12]. Although it was not the endeavour of this study to analyse the vestibular changes in goitrous hypothyroid-ism, the authors would like to highlight that almost 39% cases had a history of vertigo, out of which 26 patients had an subjective improvement after levothyroxine therapy at the end of 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…This data is significantly worrying when thinking about the harm that the reduction or absence of action of TH in the crucial periods of neurological development and maturation can bring. The central nervous system is one of the most affected ( 51 ), and it can alter the processing of the acoustic signal up to the cortex, causing difficulties in auditory skills ( 52 ) that will result in problems with behavioral, language, and social difficulties.…”
Section: Introductionmentioning
confidence: 99%